Writing Using Blogs: A Way to Engage Colombian Adolescents in Meaningful Communication - Gloria Rojas Álvarez (Profile: Issues in Teachers' Professional Development)
We report an action research project developed with ninth grade students of a public school in Bogotá, Colombia, and which focused on innovating English communication through writing blogs. The project took into account the implementation of a specific blog that proposes activities, suggestions, strategies and links, among other things, to increase communication in English. It also prompted the written production of students in the blogs when posting entries and communicating through them. Some aspects of the project were developed in the classroom; others in the computers room, and others were developed by the students independently or collaboratively with classmates. Findings show how students communicated through writing in blogs and the main characteristics of the interaction that took place when using them.